Hypertension Fails to Disrupt White Matter Integrity in Young Or Aged Fisher (F44) Cyp1a1Ren2 Transgenic Rats. Issue 2 (February 2015) - Holland, Philip R; Pannozzo, Mercede A; Bastin, Mark E; McNeilly, Allison D; Ferguson, Karen J; Caughey, Sarah; Jansen, Maurits A; Merrifield, Gavin D; Marshall, Ian; Mullins, John J; Wardlaw, Joanna M; Sutherland, Calum; et al.
Hypertension is linked with an increased risk of white matter hyperintensities; however, recent findings have questioned this association. We examined whether hypertension and additional cerebrovascular risk factors impacted on white matter integrity in an inducible hypertensive rat. No white matter hyperintensities were observed on magnetic resonance imaging either alone or in conjunction with ageing and high-fat diet. Aged hypertensive rats that were fed a high-fat diet had moderately reduced fractional anisotropy in the corpus callosum with no overt pathological features. Herein we show that moderate hypertension alone or with additional risk factors has minimal impact on white matter integrity in this model.